Experience during COVID-19 lockdown and self-managing strategies among caregivers of children with epilepsy: A study from low middle income country. (January 2021) - Wanigasinghe, Jithangi; Jayawickrama, Ashan; Hewawitharana, Gemunu; Munasinghe, Jagath; Weeraratne, Chathurika T.; Ratnayake, Pyara; Wijesekara, Dimuthu S.; Fernando, Sanjaya; Rupasinghe, Priyanka
Highlights: Face-face interview with caregivers conducted at end of a lockdown is a novelty. The data had an island wide representation. It added to the limited descriptions on difficulties faced by caregivers of children with epilepsy during COVID-19, particularly from low income settings. It described that caregivers did not experience significant stress due to the COVID-19. It identified self-management strategies adopted by parents to face a recurrence of outbreak of COVID-19. Abstract: Purpose: Abrupt halt of service provision due to pandemic state of COVID-19, significantly affected care of patients with chronic diseases like epilepsy; its impact being greater on caregivers of vulnerable groups such as children with epilepsy. We performed this study to describe difficulties posed by the lockdown to caregivers of children with epilepsy in a low-middle income country and describe their responses and self-management strategies to overcome difficulties and prepare for a recurrence. Method: A cross-sectional all-island survey was carried out at paediatric neurology centers in Sri Lanka. Data was gathered via a face-to-face interview after the lockdown period. Parental stress level was evaluated using a self-rating Stress Assessment Questionnaire. Results: Caregivers of 140 children with epilepsy from seven centers served by paediatric neurologists were interviewed. Mean duration of epilepsy was 7.9 years(SD 4). Majority were on one (52.1 %) or two (20 %) anti-seizure medications regularly. The pandemic did not affect epilepsy control in majority (87.3 %), however, signficant proportion faced difficulties over regular reviews and presecription refills. Despite difficluties, 87.1 % of parents maintained dispensing anti-seizure medications to their child regularly. Caregivers demonstrated healthy self-management strategies such as awareness on medications and access methods to healthcare during lockdown and remained confident of accessability to services. Stress was experienced in < 5%. Conclusion: Lockdown status for COVID-19 did not significantly affect the control of epilepsy in children though it posed difficulties for regular reviews and obtaining medications. Self-management strategies will help caregivers to adopt to new-normal status and potential future outbreaks.